Ensuring user anonymity in online surveys - Oleshko, I.V.; Papazov, K.O. (Radiotekhnika, 2025)
The paper addresses the pressing issue of ensuring user anonymity during online surveys. The privacy risks associated with JavaScript are analyzed, which, on the one hand, provides interactivity and convenience of surveys, and on the other hand, creates a threat of data leakage through trackers and third-party scripts. It is noted that many survey platforms integrate third-party scripts that can collect users’ personal information without their consent. The paper provides an overview of existing privacy protection tools. It was found that the most popular tool among users is the Adblock Plus browser extension. The most popular platforms for online surveys (Google Forms, SurveyMonkey, Typeform, Xoyondo and others) are analyzed in terms of their ability to ensure user privacy. It was found that the level of protection varies from completely blocking scripts to their almost unlimited use. An experimental study was conducted on the Windows 11 Pro x64 operating system using the IDE PyCharm 2024.3.1.1 (Community Edition) for writing Python code. It was found that the Ghostery tool is capable of blocking up to 87% of third-party scripts that could potentially affect user anonymity. It is shown that the Google Forms platform provides the best level of user anonymity among the considered applications. Further research on user anonymity applying machine learning methods is relevant and necessary, as it will enable more effective identification of obfuscated code.